FEATURES OF THE FORMATION OF THE PROFESSIONAL TRAINING OF THE FUTURE TEACHER OF MUSIC - Хижко, О. (Modern engineering and innovative technologies, 2023)
The article examines the issue of professional readiness, which concerns various aspects of the activity of a future music teacher. A professional profile of a music teacher as a creative specialist is offered. Achieving a creative result is ensured by th